2009
DOI: 10.1001/archsurg.2009.75
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality and Mortality in Peripheral Arterial Disease

Abstract: Background: Type D personality refers to the tendency to experience negative emotions and to inhibit selfexpression in social interaction and has been shown to be an independent predictor of mortality in cardiac disease. Information about the effects of psychological traits on prognosis is lacking in cases of peripheral arterial disease (PAD).Objective: To examine whether type D personality predicts all-cause mortality in PAD.Design: Pilot follow-up study.Setting: Vascular surgery department of a teaching hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
(50 reference statements)
5
34
0
3
Order By: Relevance
“…In addition, a further study demonstrated that Type D CHD patients had a four-fold risk of major cardiac events over five years, independent of disease severity [5]. Similar findings were demonstrated in recent studies which demonstrated a comparable relationship between Type D and mortality in patients with chronic heart failure (CHF) [6] and peripheral arterial disease (PAD) [7]. A further study found that Type D predicts death and recurrent MI in patients with acute MI after controlling for both disease and depression severity [8].…”
Section: Introductionsupporting
confidence: 74%
“…In addition, a further study demonstrated that Type D CHD patients had a four-fold risk of major cardiac events over five years, independent of disease severity [5]. Similar findings were demonstrated in recent studies which demonstrated a comparable relationship between Type D and mortality in patients with chronic heart failure (CHF) [6] and peripheral arterial disease (PAD) [7]. A further study found that Type D predicts death and recurrent MI in patients with acute MI after controlling for both disease and depression severity [8].…”
Section: Introductionsupporting
confidence: 74%
“…22,23,25,27 Type D personality was also associated with an odds ratio Ն2.3 in heart failure, 28 heart transplantation, 29 and peripheral arterial disease. 30 There was no significant heterogeneity among these studies on prognosis, (Qϭ6.6, dfϭ8, PϽ0.001, I 2 ϭ0.0%), indicating that the pooling of studies was warranted.…”
Section: Type D Personality and Prognosismentioning
confidence: 92%
“…Williams et al compared males with and without Type D personality and found that the former group exhibited a significantly higher cardiac output during a stress condition. However, there was no relationship between Type D personality and cardiovascular reactivity in females [30]. It has been reported that 13-24% of individuals in a healthy adult population can be classified as a Type D personality.…”
Section: Discussionmentioning
confidence: 80%